Hybrid tools of generating unit simulation for proper tuning of automatic voltage regulators: concept, development and validation; Electrical engineering; Vol. 104, iss. 3 - Askarov A. B. Alisher Bakhramzhonovich; Andreev M. V. Mikhail Vladimirovich; Gusev A. S. Alexander Sergeevich; Rudnik V. E. Vladimir Evgenevich (2021, 2021)
Title screen